The impact of the new regulations on the rules of professional conduct for nurses (part I) - Zimmermann, Agnieszka; Banasik, Przemysław (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Working as a nurse is regulated by law. At the turn of 2011 and 2012 the legislature made several regulatory changes that, by introducing new powers and responsibilities, have impact on the rules of professional conduct for nurses. The analysis of the particular acts of law allowed for a summary of the new or the revised rules of conduct. This paper makes an attempt to systematize the modifications of the law, bearing in mind the aspect of usefulness for the practical use.